¿Un encargado de prevención puede tener responsabilidad penal? - Palao Vizcardo, Erick (2024)
This paper seeks to analyse how the highest administrative body of a legal entity assigns functions to the prevention officer to manage the risks that may generate criminal liability for said organisation. It also examines how the prevention officer can assume a guarantor position if he is delegated powers that allow him to make decisions with autonomy and independence. In such a case, he could have criminal liability, either as author or participant, in the degree of complicity, for his own acts or for third parties linked to the legal entity.